Why Militant Groups Fight Each Other: The Role of Support, Political Objectives and Revenge - Eric van Um (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Most of the research on terrorism studies the relationship between militant groups and targeted states. This means that we actually know little about the role of violence in intergroup relationships. Previous research has claimed that such forms of violence occur regularly but underlying patterns and motives remain under-researched. This paper seeks to advance understanding of inter-terrorist group violence both among groups with shared and competing objectives. It particularly aims to analyze the characteristics of inter-group violence and also tries to determine if such violence reflects strategic decision-making or if it rather stems from expressive motives. The paper uses a mixed method approach which combines quantitative and qualitative analyses for a sample of countries. Data is primarily obtained from the Global Terrorism Database (GTD) and complemented with further datasets, reports and other qualitative sources. Results indicate that inter-group violence has taken place both among terrorist groups with competing and shared objectives but remained limited in absolute numbers. The low levels of incidents do not mean that disputes have not arisen but competition has rather unfolded on a verbal level or as low-level violence including intimidation and exiling. A case study on Northern Ireland is then used to elaborate on the particular drivers and dynamics of such violence. Results further show that violence among militants has mostly been driven by strategic considerations of the actors involved. When groups clashed it was usually for a purpose beyond emotional satisfaction and regularly related to a fight for support and influence.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330